A guide to EU environmental law - Zeben, Josephine A. W. van, 1984-; Rowell, Arden (University of California Press, 2021)
"Written by a team of internationally respected authors, this unique primer distills the European Union's environmental law and policy into a practical guide for a non-legal audience, as well as for lawyers trained in other jurisdictions. The first part of the book explains the basics of the European legal system: key actors, types of laws, and overarching legal strategies for environmental management. The second part delves into specific environmental issues-pollution, ecosystem management, climate change-and how EU law addresses these. Each chapter includes informative "spotlights" offering brief overviews of topics or excerpts from laws, as well as summaries of key concepts and discussion questions. With a highly accessible structure and useful illustrative features, the book provides a long-overdue resource on environmental law for students and for those who work in environmental policy or environmental science"--